2022
DOI: 10.3390/cancers15010148
|View full text |Cite
|
Sign up to set email alerts
|

Controversies and Opportunities in the Clinical Daily Use of the 21-Gene Assay for Prognostication and Prediction of Chemotherapy Benefit in HR+/HER2- Early Breast Cancer

Abstract: Several multigene assays have been developed to help clinicians in defining adjuvant treatment for patients with hormone-receptor-positive (HR+), human epidermal growth factor receptor-2 (HER2)–negative early breast cancer. Despite the 21-gene assay having been available for decades, it has only recently been included in the healthcare systems of several countries. Clinical optimisation of the test remains of critical interest to achieve a greater impact of genomic information in HR+/HER2- early breast cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In addition, Oncotype DX is considered the genomic assay of choice worldwide and its primary purpose is to assess the risk of early HR+/ HER2− BC local and distant recurrence so that patients could be exempted from receiving ACT. However, it has the disadvantages of high price and uncertainty 23. Using data from a large sample based on the SEER database, this study concluded that further age stratification was necessary for older women with HR+/HER2− BC over 65 years of age.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, Oncotype DX is considered the genomic assay of choice worldwide and its primary purpose is to assess the risk of early HR+/ HER2− BC local and distant recurrence so that patients could be exempted from receiving ACT. However, it has the disadvantages of high price and uncertainty 23. Using data from a large sample based on the SEER database, this study concluded that further age stratification was necessary for older women with HR+/HER2− BC over 65 years of age.…”
Section: Discussionmentioning
confidence: 96%
“…However, it has the disadvantages of high price and uncertainty. 23 Using data from a large sample based on the SEER database, this study concluded that further age stratification was necessary for older women with HR+/HER2− BC over 65 years of age. According to our age classification, ACT improved the prognosis of patients aged 65–79.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important unanswered question is whether OFS can replace adjuvant chemotherapy in intermediate-risk, endocrine-responsive early breast cancer. The use of genomic assays, such as OncotypeDX and MammaPrint, has revolutionized adjuvant treatment decisions in BC, but their applicability in premenopausal patients, especially those under 40 years with node-positive disease, is still debated [ 59 , 60 ]. This is mainly because trials testing genomic assays have had a limited representation of women under the age of 40 years and premenopausal women included in these trials predominantly received tamoxifen alone as adjuvant endocrine therapy [ 61 ].…”
Section: Indications To Ofs In Early Breast Cancermentioning
confidence: 99%